A Study on Brand Personality and Experience in Early Morning Delivery as a New Distribution Service - 이장석; 김진환 (Journal of distribution science, 2020)
Purpose: Early morning delivery markets have grown exponentially in the last few years. This study aims to verify the effects of brand experience factors and brand personality factors of Market Kurly, a representative early morning delivery brand, on brand attachment and brand loyalty. Research design, data, and methodology: For this purpose, 204 ordinary people in their 20s and 40s who have experience in using Market Kurly were surveyed. 7 hypotheses were verified by using hierarchical regression analysis. Results: Affective experience, intellectual experience, and behavioral experience among brand experience factors had a positive effect on brand attachment. Also, brand personality-self-image congruence and brand personality-human brand congruence as brand personality factors had a positive effect on brand attachment. The brand attachment was identified as an important preceding factor to explain the brand loyalty of Market Kurly. Conclusions: When applying brand experience factors to the early morning delivery service context, each brand experience factor affected brand attachment and brand loyalty. The scope of research on brand personality-self-image congruence was expanded in that it considered both brand personality-human brand congruence and brand personality-self-image congruence. This study provides academic and practical implications by revealing that brand experience factors and brand personality factors can positively affect brand attachment and brand loyalty. KCI Citation Count: 1